Understanding student simultaneous smartphone use in learning settings: A conceptual framework. (3rd August 2020) - Fu, En; Gao, Qiufeng; Wei, Chuqian; Chen, Qianyi; Liu, Yijun
Abstract: Smartphone use in learning settings is a common behaviour amongst college students. Building on the theory of consumerism, self‐efficacy and addictive behaviours, the current study developed a three‐component conceptual framework to understand college students' smartphone use in organizational as well as self‐directed learning settings. One thousand and thirty‐three students in Shenzhen completed an online survey that measured their frequency of using smartphones in learning settings, motivation for using smartphones in learning settings, behavioural control self‐efficacy, smartphone use time, problematic smartphone use, multitask habit and impulsiveness. Regression and configurational analytical approaches were used to examine linear and nonlinear relationships. Results support the use of the proposed framework to explain students' smartphone use behaviour in learning settings. Lay Description: What is currently known about the subject matter: Smartphone usage in learning settings (SUL) is common in college students. Consumption values can explain students' smartphone use in learning settings. Most of students' technology use behaviours are automatic bodily habits. Self‐efficacy regulates many learning‐related behaviours. What this paper adds to the subject: Used value, habit and self‐efficacy (VEH) factors to explain SUL. Value and habit factors have combined instead of independent effects on SUL. SUL could involve distractive or educational smartphone use. Different psychological mechanisms underly distractive versus educational use. The implications of study findings for practitioners: Nurturing study‐oriented values in students can help prevent distractive SUL. Inhibiting technology‐related bodily habits can reduce distractive SUL. Nurturing low SUL self‐efficacy can reduce SUL behaviours. Individual difference should be considered in SUL intervention.